Characteristics of Tasawwuf Texts in the Traditional Pallidars Curriculum of Malabar - Hassan Shareef KP; Nasimudheen MP (Lembaga Peneltian Universitas Islam Internasional Darullughah Wadda'wah, 2026)
This study examines the characteristics of Tasawwuf texts within the curriculum of the Islamic traditional education system in Malabar, South India, known as Pallidars. It addresses a scholarly gap concerning both their role in moral and ethical divine education and the significance of the region’s traditional Islamic education system. Employing a qualitative methodology, the study combines content analysis of multiple key Tasawwuf works with interviews of expert scholars, drawing from local vernacular sources. The study centres on the research question “How does Pallidars curriculum fix the Tasawwuf texts for moral and ethical divine education in Malabar regions?” to comprehensively examine the characteristics, teaching methods, and effectiveness of the Tasawwuf texts which is categorized into foundational, intermediate, and advanced levels, each featuring distinct texts that progressively deepen spiritual knowledge and practice. Findings reveal that the Pallidars curriculum effectively promotes applied spirituality and ethical living rather than rote memorization, supported by pedagogical methods emphasizing practical implementation. Biographical insights into the authors enrich understanding of the intellectual heritage underpinning the curriculum. Overall, the study highlights the Pallidars system’s enduring contribution to sustaining spiritual and ethical values in Malabar’s Muslim community through a structured, multi-text Tasawwuf education.